Trend of Cutaneous Leishmaniasis in Kermanshah Province, West of Iran from 1990 To 2012 - HAMZAVI, Yazdan (Iran J Parasitol, 2015)
BACKGROUND: This study was conducted to explain the trend of Cutaneous Leishmaniasis (CL) in Kermanshah Province, western Iran from 1991–2012. METHODS: In this analytical-descriptive study, all of the patients suspected to CL in Kermanshah Province were studied. Smears were prepared from most of them, stained with Giemsa, and examined microscopically for Leishman bodies. A few of the patients were diagnosed according to physician diagnosis and response to glucantime. Questionnaires were completed for all of them. Collected data were analyzed using SPSS-21 and Spearman and Kendall tests. RESULTS: From 1991 to 2012, 1684 cases of CL were recorded. In the years 2011–12 the frequency of CL in the province reached to 7.4/100,000, which showed a remarkable increase in the frequency of new cases CL in the province. In the years 2011–12 about 47% of total cases of CL in the province, was seen in Ghasr-e-Shirin district,which the frequency of CL in this district reached to 264.5/100,000. Frequency of CL in males and females was 57% and 43% respectively. The most cases of CL were seen in housewives (32.1%) and age groups of 20 to 29 years old (19.9%). In addition, the most cases of disease were seen in winter (41.8%) and fall (28.9%). CONCLUSION: CL is increasing remarkably in warm climates of the province, and Ghasr-e-Shirin must be of particular interest, as the most infected district in the province.